Directional Reconstruction of Spent Lithium Cobalt Oxide by Microwave Plasma: Efficient Oxygen Evolution Catalyst from Closed‑Loop Recovered Resources - Chen, Chao; Zhu, Qixuan; Shan, Minghui; Cheng, Lei; Wang, Weiwei; Lu, Zhiqiang; Wang, Yi; Sun, Hengda; Yamauchi, Yusuke; Tang, Jing; Xu, Guiyin (Nano-Micro Letters, 2026)
The key challenge of water electrolysis is the high energy barrier of the oxygen intermediate of the oxygen evolution reaction (OER) and the unclear catalytic active sites. The recycling of valuable metals from spent batteries and their reconstruction into high-performance electrolytic water catalysts offers significant economic and environmental benefits. In this work, we report a Co3O4/NiFe-layered double hydroxide heterostructure electrocatalyst by reconstruction of spent LiCoO2 cathode material through microwave plasma treatment and then compositing with NiFe-layered double hydroxides through a simple hydrothermal method. This catalyst achieves a low overpotential of 235 mV at 10 mA cm−2 for OER and exhibits prolonged stability at high current densities when integrated into an alkaline electrolyzer, which surpasses commercial IrO2. In situ spectral analysis and density functional theory demonstrate that the presence of heterostructures between Co3O4 and NiFe-LDH optimizes the charge transport path and reduces the interface resistance. Specifically, the charge redistribution optimizes the adsorption energy of oxygenated intermediates on the Ni and Fe sites, thereby optimizing the reaction pathway and significantly improving the overall OER catalytic efficiency. This work provides a green and scalable way to convert spent metal sources into high-value electrocatalysts, while addressing critical challenges in energy storage and sustainable hydrogen production. Highlights: 1 A closed-loop recycling route for spent LiCoO2 batteries, converting metal resources into high-value electrocatalysts with environmental and economic merits. 2 Synergistic microwave plasma etching and hydrothermal method enable precise construction of Co3O4/NiFe-LDH heterostructures, optimizing material surface and interface properties. 3 Charge redistribution at the heterointerface regulates oxygen intermediate adsorption, providing a new interfacial engineering idea for low-cost water electrolysis catalysts.